2023
DOI: 10.1002/nbm.4900
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated radiofrequency safety concept for implant carriers in MRI based on sensor‐equipped implants and parallel transmission

Abstract: To protect implant carriers in MRI from excessive radiofrequency (RF) heating it has previously been suggested to assess that hazard via sensors on the implant. Other work recommended parallel transmission (pTx) to actively mitigate implant‐related heating. Here, both ideas are integrated into one comprehensive safety concept where native pTx safety (without implant) is ensured by state‐of‐the‐art field simulations and the implant‐specific hazard is quantified in situ using physical sensors. The concept is dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 132 publications
0
12
0
Order By: Relevance
“…In addition to ensuring RF safety, optimizations can be performed to improve image quality when an implant is present. Simulations have shown that using this strategy with an eight‐channel body coil at 3T, mean B1+$$ {B}_1^{+} $$ can be increased three‐fold compared to CP excitation, while still maintaining a maximum temperature increase of the implant tip of ≤1 K 67 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to ensuring RF safety, optimizations can be performed to improve image quality when an implant is present. Simulations have shown that using this strategy with an eight‐channel body coil at 3T, mean B1+$$ {B}_1^{+} $$ can be increased three‐fold compared to CP excitation, while still maintaining a maximum temperature increase of the implant tip of ≤1 K 67 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the demonstrated feasibility in this study, it is possible to establish a comprehensive safety strategy that includes native pTx safety (without implant). 42,67 Native pTx safety can be ensured through state-of-the-art electromagnetic field simulations conducted on human voxel models to calculate Q-matrices in advance, which enable the generation of safe excitation vectors. In the presence of an implant in a patient, the Q S of the implant can be measured in situ, transmitted to the MRI system, and combined with the native safety Q-matrices.…”
Section: Comprehensive Implant Safety Conceptmentioning
confidence: 99%
See 3 more Smart Citations